Reducing the Effect of Functional Disability on Life Satisfaction Among Persons With a Lived Experience of an Infectious Viral Disease in Taiwan: A Tri-Mediation Model. (April 2022) - Wang, Ming Hung; Brooks, Jessica Marie; Iwanaga, Kanako; Wu, Jia Rung; Chen, Xiangli; Lee, Beatrice; Rumrill, Stuart; Chan, Fong
The purpose of the study was to examine whether disability acceptance, hope, and resilience mediate the relationship between functional disability and life satisfaction in people with a lived experience of an infectious viral disease (i.e., polio and postpolio syndrome [PPS]). Participants consisted of 157 individuals diagnosed with polio or PPS who were recruited from two community support organizations in Taiwan. Participants completed self-report questionnaires. Data were analyzed with a simultaneous regression analysis. The tri-mediation model indicated that disability acceptance, hope, and resilience were associated with life satisfaction, accounting for a large effect size of 46% of the variance in the life satisfaction scores. The direct effect of functional disability on life satisfaction became insignificant when the mediators were controlled for in the model. Hope, disability acceptance, and resilience were found to fully explain the association between functional disability and life satisfaction. This study demonstrated that positive psychosocial factors might help to buffer the indirect and direct negative effects of functional disability on life satisfaction. Implications of these findings for future research and clinical practice when supporting individuals with a lived experience of an infectious viral disease, including COVID-19, are discussed.